If the equation above holds true for constants and , which of the following options must be true?
Notation: denotes the set of all real values .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since the limit is in the form of 1 ∞
Now, Generalised formula for 1 ∞ if x → a lim f ( x ) = 1 and x → a lim ± ∞ is
x → 0 lim ( f ( x ) ) g ( x ) = e lim x → 0 g ( x ) ( f ( x ) − 1 )
Considering f ( x ) = 1 + a x + b x 2 and g ( x ) = x 2
Applying above formula x → 0 lim ( 1 + a x + b x 2 ) 2 / x = e lim x → 0 x 2 ( a x + b x 2 )
According to the question , e lim x → 0 x 2 ( a x + b x 2 ) = e 3
Comparing the exponents, we get
⟹ x → 0 lim x 2 ( a x + b x 2 ) = 3
⟹ x → 0 lim 2 a + 2 b x = 3 ⟹ 2 a + 2 b ( 0 ) = 3
⟹ 2 a = 3 ⟹ a = 1 . 5 , b ∈ R